Source and symptoms of COVID-19 among hospital workers in Milan. (3rd December 2020) - Mandić-Rajčević, S; Masci, F; Crespi, E; Franchetti, S; Longo, A; Bollina, I; Velocci, S; Amorosi, A; Baldelli, R; Boselli, L; Negroni, L; Zà, A; et al.
Abstract: Background: Healthcare workers (HCWs) are commonly infected by SARS-CoV-2 and represent one of the most vulnerable groups. Adequate prevention strategies are necessary to guarantee HCWs' safety, as well as to prevent dissemination of the infection among patients. Aims: To describe a case series of SARS-CoV-2-positive HCWs in a large public healthcare organization in Milan (Italy) during the most devastating weeks of the epidemic and analyse the sources, symptoms and duration of SARS-CoV-2 infection. Methods: This study included 172 SARS-CoV-2-positive HCWs who were infected between the 25th of February and the 7th of April 2020. A nasopharyngeal swab (NPS) and RT-PCR were used to indicate. Results: Initially, the most common sources of infection were other positive HCWs (49%). Medical doctors and nursing assistants were most frequently infected, with infection rates of 53/1000 and 50/1000, respectively. COVID-19 departments were less affected than internal medicine, surgery, intensive care, or emergency room. The most commonly reported symptom was mild cough, while loss of smell (anosmia) and loss of taste (ageusia) were reported as moderate and severe by 30–40% of HCWs. The time necessary for 50% of workers to recover from the infection was 23 days, while it took 41 days for 95% of HCWs to become virus-free. Conclusions: HCWs are commonly infected due to close contacts with other positive HCWs, and non-COVID departments were most affected. Most HCWs were asymptomatic or subclinical but contact tracing and testing of asymptomatic HCWs help identify and isolate infected workers.